The dignity of the frail: on compassion, terror and social death - Hordern, J (Johns Hopkins University Press, 2021)
This enquiry considers how the dignity of the frail elderly is objectively grounded, socially constructed, and subjectively experienced. The lives of the frail trouble public consciousness. A terror of old age, felt by young or old, is liable to form a toxic affective culture of social death. Against such threats, the dignity of the frail requires defense. However, empathy- and capacities-based approaches to dignity fail to give a compelling account of humanity’s membership in shared community. By contrast, the poetry of the Psalms and New Testament puts terror to flight by articulating how dignity is found within God’s steadfast, worth-bestowing love which tenderly accompanies humanity in its shared dustiness from the womb to old age and beyond. The blessed dignity these sources describe is found to be more conceptually robust and affectively compelling than an individualistic eudaimonism. Cultivating an ecology of dignity in practice is finally shown to depend on a compassion which grows from the same fertile, imaginative ground.